Right Heart Failure during Veno-Venous Extracorporeal Membrane Oxygenation for H1N1 Induced Acute Respiratory Distress Syndrome: Case Report and Literature Review - Seung-Hun Lee (Korean Journal of Thoracic and Cardiovascular Surgery, 2015)
A 38-year-old male was admitted with symptoms of upper respiratory infection. Despite medical treatment, his symptoms of dyspnea and anxiety became aggravated, and bilateral lung infiltration was noted on radiological imaging studies. His hypoxemia failed to improve even after the application of endotracheal intubation with mechanical ventilator care, and we therefore decided to initiate venovenous extracorporeal membrane oxygenation (VV ECMO) for additional pulmonary support. On his twentieth day of hospitalization, hypotension and desaturation (arterial saturated oxygen ＜85%) developed, and right ventricular failure was confirmed by two-dimensional echocardiography. Therefore, we changed from VV ECMO to venoarteriovenous (VAV) ECMO, and the patient ultimately recovered. In this case, right ventricular dysfunction and volume overloading were induced by long-term VV ECMO therapy, and we successfully treated these conditions by changing to VAV ECMO.